A geomorfologia no Brasil na década de 80 do século XX: uma análise a partir de eventos científicos - Abreu, Carlos Felipe Nardin Rezende de (2016)
This study seeks to understand the development of brazilian geomorphology from the 1980s, using as a basis of understanding the geography applied physics symposiums, occurred in 1984, 1986 and 1989. Such events have been created in an attempt to promote new dialogues that aimed to discuss what steps should be covered by the field of physical geography and consequently of geomorphology. Before entering the discussion proposal is an effort of comprehension of the paths taken by science geography is necessary, since its institutionalization in the 1930s to date proposed in the research, trying to understand how the introduction of geomorphology discipline was made in their curriculum, its development and its importance during his decades. In this attempt to understand it uses the concept of "scientific field" of the french sociologist pierre bourdieu, and science for it understood as a local dispute that guarantee the scientific capital accumulation and consequently greater power of decision within the scientific field, in our specific case of the geography, in this scientific field we find times when the dominated groups become dominant. In this conceptual adoption seeks to observe the moment of transition of power within the science in question, it is also necessary to understand the historical context from that of the various contexts, citing the political, economic and social.